Synthesis, Characterization of Some 6/8 Substituted 2-Chloro-3- Formyl Quinoline Incorporated,3-Thiazoles/1,3-Benzothiazoles And Their Biological Studies - Vineetha Telma D’Souza, Janardhana Nayak, Desmond Edward D’Mello, Dayananda P. (International Journal of Advanced Science and Technology, 2020)
A new series of  Ethyl 2- {(E)- [(2-chloro- quinolin - 3-yl) methylidene]amino} -4- methyl -1, 3- thiazole -5- carboxylate / (E)-1- (2-chloro quinolin -3-yl )-N-(5-nitro -1,3-thiazol -2- yl)methanimine / (E)-N- (1,3-benzo thiazol-2-yl)-1- (2-chloro quinolin-3-yl) methanimine were obtained by the reaction of 6/8-substituted-2-chloro-3-formyl quinolines and ethyl amino-methyl-thiazole-carboxylate / nitro-thiazol-amine / benzothiazol-amine. The novel chloro- formyl quinoline-1,3-thiazole/1,3-benzothaizole series were proved by Mass, NMR and IR spectroscopy. The novel quinoline -1,3-thiazole /1,3-benzothaizole derivatives showed antimicrobial activities. The series showed tremendous biological activiies.